Pengaruh Jenis Material Pipa Pendingin Terhadap Distribusi Temperatur di Dalam Beton Yang Didinginkan dengan Sistem Post Cooling - Ratnawati (Jurnal Teknik Juara Aktif Global Optimis, 2021)
Mass concrete is a concrete casting with a large enough volume, usually used for foundations, bridges,dams and so on. The heat of hydration in the mass concrete causes a temperature difference between the inside and the outside of the concrete surface. This can cause cracks in the concrete,where the temperature inside the concrete has a higher temperature rise than the outer surface yhat is in contact with the environment. One way to control the temperature of the concrete is to use a post cooling system.Post cooling system design requires knowledge of temperatur distribution in concrete. The research was conducted by varying the cooling pipe materials used,namely steel,PVC,and PEX where the cooling water discharge and temperatur were constant.The result of the research that have been carried out show that with the same cooling water discharge and temperature,concrete with PVC cooling has a higher temperature than PEX cooling pipe or steel.